2010
DOI: 10.1517/17425251003781912
|View full text |Cite
|
Sign up to set email alerts
|

Ambient tonicity and intestinal cytochrome CYP3A

Abstract: In vitro hypertonicity of ambient osmotic environment in cultured human cells increases expression of CYP3A through transcriptional enhancement by osmosensitive NFAT5. Although post-prandial osmolality in the GI lumen in vivo is substantially increased, NFAT5 activation has not been reported. Similarly, high-salt diet increases intestinal CYP3A function in humans, but it is not known whether these changes are mediated directly by NFAT5.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 98 publications
(83 reference statements)
0
3
0
Order By: Relevance
“…B) in db/db mice. In vitro studies have shown that hypertonicity of ambient osmotic environment in cultured intestinal human cells increases expression of CYP3A (Chuang and Ito ). Furthermore, after spontaneous ingestion of solid food with free access to water, rodent intestinal osmolality may reach 600–800 mOsm kg −1 , which is at least a twofold increase compared with the measured plasma osmolality of 300 mOsm kg −1 (Osaka et al.…”
Section: Resultsmentioning
confidence: 99%
“…B) in db/db mice. In vitro studies have shown that hypertonicity of ambient osmotic environment in cultured intestinal human cells increases expression of CYP3A (Chuang and Ito ). Furthermore, after spontaneous ingestion of solid food with free access to water, rodent intestinal osmolality may reach 600–800 mOsm kg −1 , which is at least a twofold increase compared with the measured plasma osmolality of 300 mOsm kg −1 (Osaka et al.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, hyper-tonicity-induced HMOX1 expression is observed under conditions in which NFAT5 is known to be activated (68). NFAT5 is a potent regulator of cytochrome P450 3A (CYP3A) family members (69). CYP proteins are heme-containing mono-oxygenases that are principally responsible for metabolizing xenobiotics and toxins.…”
Section: Hyperosmotic Stress and Adaptive Responsementioning
confidence: 99%
“…Cells within the kidney (renal inner medula), the gastrointestinal tract, the cornea, the liver, intervertebral discs and joints are exposed to substantial osmolarity fluctuations even under physiological conditions (reviewed in 6 ). In addition, dietary and ambient conditions can also induce hypernatremia in sites such as the respiratory epithelium and the skin, resulting in approximate hyperosmolalities of 400 mOsm/kg 7 8 9 . Hyperosmotic stress acts as an inflammatory stimulus and is implicated in various pathophysiological conditions.…”
mentioning
confidence: 99%